Melatonin ameliorated CUMS-induced depression-like behavior via restoring endoplasmic reticulum stress in rat hippocampus. Issue 1 (6th January 2021) - Wang, Shengdong; Xu, Xiaohong; Ju, Xuan; Wang, Shuqi; Li, Jing; Yan, Pan; Yu, Zhenghe; Song, Mingfen
Abstract : Melatonin is a hormone synthesized and secreted by the pineal gland with the effect of regulating sleep rhythm. Circadian and sleep disturbances may be central for understanding the pathophysiology and treatment of depression. Recently, the melatonergic system has been implicated in the pathophysiology and treatment of depression. In this study, we observed the effects of melatonin on depression-like behavior induced by chronic unpredictable mild stress (CUMS) in rats, and its molecular mechanism was explored. Adult male Sprague–Dawley rats were exposed to CUMS for 4 weeks. Melatonin or saline was injected intraperitoneally. Behavioral changes of Sprague–Dawley rats were detected by the open field test, sugar preference test, elevated O maze test and forced swimming test. In addition, the plasma corticosterone level and the expression of endoplasmic reticulum stress-related protein in the hippocampus of rats were measured. Compared with the control group, the CUMS-exposed Sprague–Dawley rats showed depression-like behavior, which was significantly improved by melatonin treatment. Moreover, CUMS induced endoplasmic reticulum stress and JNK phosphorylation in the hippocampus. Melatonin treatment could significantly reverse the endoplasmic reticulum stress and JNK phosphorylation induced by CUMS. These results suggest that melatonin improves depression-like behavior by inhibiting endoplasmic reticulum stress induced by CUMS. This study demonstrates that melatonin can improve depression-like behavior induced by CUMS, which may be related to the inhibition of endoplasmic reticulum stress and JNK phosphorylation in rat hippocampus.